PENGEMBANGAN PROTOTIPE STASIUN OBSERVASI MARITIM NEAR REAL TIME DI KAWASAN RENCANA NATIONAL SCIENCE TECHNOPARK MARITIME, PENAJAM PASER UTARA - Endro Soeyanto; Agus Sudaryanto; Rizki Adi Nugroho (Laboratory for Marine Survey Technology, 2020)
[Prototype Development of Near Real Time Maritime Observation Station at Regional of ProposedNational Science Technopark Maritime, Penajam Paser Utara] Environmental monitoring efforts including oceanographic conditions and their interactions with the atmosphere are important inefforts to provide data and information for the use, protection and management of the maritime environment. Fulfillment of a continuous and near real-time monitoring system becomes a necessity.Penajam Paser Utara Region has been designated as the location of National Science TechnologyPark - Maritime (NSTP-M) development which facilitated by a maritime observation stationinfrastructure. By combining various subsystems, including data acquisition, data distribution and power supply management, this study aims to provide an overview of the development of monitoring system and the data generated from the maritime observation stations. As the result, the maritime observation station has been able to monitor weather parameters, tides and surface currents continuously and near real time (nRT) by adopting the Meteorological-Oceanographic (Met-Ocean) survey which is integrated in the Read Down Station (RDS) as data processing and management center in BPPT. Keywords: Maritime Observation Station, Meteorology-Oceanography Survey, NSTP Maritime, District of Penajam Paser Utara